Prolactin is associated with bone mineral density in subjects with type 2 diabetes mellitus - Chen, Jia; Liu, Geng; Li, Quan; Deng, Wei (Frontiers in Endocrinology, 2022)
Purpose: Prolactin (PRL) exerts actions in bone besides lactation and reproduction. This study aimed to investigate whether PRL is related to bone mineral density (BMD) in type 2 diabetes mellitus (T2DM). Methods: 642 patients with T2DM were divided into two groups: mildly increased PRL (HP group, n=101) or normal PRL (NP group, n=541). BMD was measured by dual-energy X-ray absorptiometry and compared. Results: 1) BMD, T score at lumbar spine L1-4, right hip and femur neck, and Z score at femur neck were significantly higher in HP than NP group (0.96±0.16 vs. 0.92±0.15g/cm2, P=0.019; 0.88±0.15vs. 0.84±0.14 g/cm2, P=0.007; 0.75±0.17 vs.0.70±0.13 g/cm2, P=0.001; -0.90(-1.85, -0.20) vs. -1.40(-2.20, -0.40), P=0.018; -0.80(-1.50, -0.30) vs. -1.10(-1.80, -0.53), P=0.026; -1.30(-2.00, -0.60) vs. -1.70(-2.20, -1.00), P=0.001; -0.20(-0.70, 0.30) vs. -0.40 (-0.90, 0.10), P=0.026). In males, T, Z score at right hip and femur neck were significantly higher in HP than NP group (-0.70(-1.32, 0.20) vs. -0.90(-1.50, -0.40), P=0.038; -0.20(-0.80, 0.20) vs. -0.50(-0.10, 0.10), P=0.027; -0.30(-0.60, -0.30) vs. -0.40(-0.90, 0.20), P=0.038) while not in females. 2) BMD at right hip, Z score at right hip and femur neck were significantly positively associated with PRL (r=0.087, P=0.029; r=0.089, P=0.024; r=0.087, P=0.029). In males, BMD at L1-4 and right hip, T score at L1-4, right hip and femur neck, Z score at right hip and femur neck were significantly positively associated with PRL (r=0.122, P=0.007; r=0.105, P=0.041; r=0.123, P=0.016; r=0.110, P=0.032; r=0.115, P=0.025; r=0.121, P=0.018; r=0.138, P=0.007) while not significant in females. 3) Males divided into two groups according to T score(T score at right hip＞-1 or T score at right hip≤-1) or median of BMD at L1-4, right hip or femur neck, PRL were significantly higher in higher BMD than lower BMD group(16.32±6.12 vs. 14.78±5.68 ng/ml, P=0.012; 16.20±6.21 vs. 14.73±5.40 ng/ml, P=0.014; 16.10±6.01 vs. 14.80±5.77 ng/ml, P=0.032; 16.17±6.04 vs. 14.76±5.77 ng/ml，P=0.02; 16.48±6.05 vs. 14.98±5.81 ng/ml, P=0.020; 16.10±5.98 vs. 14.80±5.87 ng/ml, P=0.035). Conclusion: Increased PRL was associated with better BMD in patients with T2DM, especially in males. PRL within the biologically normal range may play a protective role in the BMD of T2DM.